Transcriptome analysis of the immature inflorescences of foxtail millet treated with Sq-1 for inducing male sterility (Bangladesh Journal of Botany, 2021)
A comparative transcriptomic analysis was carried out through next-generation sequencing technology for the SQ-1-treated immature inflorescences of foxtail millet (Setaria italica). It was found that 96.7% of the pollen of SQ-1-treated plants were sterile, thereby confirming the efficacy of SQ-1 in inducing male sterility in foxtail millet. A total of 6659 DEGs were identified from the plants of 2nd days of treatment, among which 3532 and 3127 were up- and down-regulated, respectively. Comparatively fewer DEGs, 1584 and 2654, were detected from the plants of 4th and 6th days of treatment, respectively. The gene expression profiles of foxtail millet were verified through qRT-PCR in accordance to 16 previously reported genes from other crops that were associated with pollen development. Reference genes Si002651 and Si002929 were found to be the most proper option for SQ-1 treatment.Bangladesh J. Bot. 50(3): 887-894, 2021 (September) Special